Profil Jumlah Leukosit Dan Suhu Tubuh Penderita Demam Tifoid Di RSUD Karanganyar - Gayatri, Arum Aditya, Dr. Mochammad Wildan, Sp.A (2017)
Typhoid fever is an acute systemic infection disease caused by Salmonella typhi and paratyphi. The clinical manifestation could be fever, complaints of central nervous system, and gastrointestinal disturbances. The prominent clinical manifestations include fever more than 7 days. The examination of the leukocyte number can be leukopenia, normal, or leukocytosis. This research purposed is to find out the profile of leukocyte number and body temperature of typhoid fever patients. This study uses descriptive observational research design with study case design and random sampling technique. The samples of this study are 107 medical record of typhoid fever patients. The research data is analyzed using a computer program Statistical for Social Science (SPSS) versi 21.0 for windows. Based on the analysis of the number of leukocyte, 44,9% (48 persons) leukopenia, 38,3% (41 persons) normal leukocyte, 16,8% (18 persons) leukocytosis. On the body temperature measurement, 15,9% (17 persons) with normal body temperature, 80,4% (86 persons) fever, and 3,7% (4 persons) high fever. On the typhoid fever patients, 44,9% (48 persons) leukopenia and 80,4% (86 persons) fever. Keyword: Typhoid fever, leukocyte count, body temperature